2011
DOI: 10.1111/j.1751-7176.2011.00508.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme Inhibitors

Abstract: J Clin Hypertens (Greenwich). 2011;13:667–675. ©2011 Wiley Periodicals, Inc. Key Points and Recommendations  In addition to hypertension, angiotensin‐converting enzyme inhibitors are indicated for treatment of patients at high risk for coronary artery disease, after myocardial infarction, with dilated cardiomypathy, or with chronic kidney disease.  The most familiar angiotensin‐converting enzyme subtype, angiotensin‐converting enzyme‐1 (kininase II), cleaves the vasoconstrictor octapeptide angiotensin II from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 94 publications
0
60
0
10
Order By: Relevance
“…The major side effects are cough, hyperkalemia and less often angioedema [24]. In the present study, dry cough was the most common ADR event.…”
Section: Discussionmentioning
confidence: 74%
“…The major side effects are cough, hyperkalemia and less often angioedema [24]. In the present study, dry cough was the most common ADR event.…”
Section: Discussionmentioning
confidence: 74%
“…Clinical trials have consistently revealed that they are safe in the post-myocardial infarction period and, subsequently, with a very low risk of significant side effects. These records endorse the recommended role of ACEIs as first-line agents in cases with diabetes who are at a particularly high risk for cardiovascular consequences, including those peoples who previously had myocardial infarction, heart failure and kidney disease (Brown & Vaughan, 1998;Gerstein, 2000;Izzo & Weir, 2011;Helal & Lane, 2014).…”
Section: Angiotensin-converting Enzyme Inhibitorsmentioning
confidence: 91%
“…The results of intravenous infusion of angiotensin I on blood pressure in the studied groups showed that induction of hypertension significantly increased response to dilute doses of angiotensin I. Angiotensin I does not have direct biological effects and it should be converted to angiotensin II by ACE to act its roles (32). Therefore, probable causes of these changes can be increasing of ACE activity and/or increasing of angiotensin II receptors.…”
Section: Discussionmentioning
confidence: 99%